Rationale and design of the Hepatocellular carcinoma Early Detection Strategy study: A multi-center longitudinal initiative of the National Cancer Institute’s Early Detection Research Network - Borges, Kelly A. (Contemp Clin Trials, 2018)
BACKGROUND: Hepatocellular carcinoma (HCC) is a common malignancy with a steadily rising incidence and associated morbidity and mortality. Cirrhosis of the liver is presently the leading risk factor for developing HCC. Abdominal imaging, with or without alpha-fetoprotein (AFP) testing, every 6 months is the current surveillance strategy for patients at risk. The available biomarkers for detecting this cancer at an early stage have inadequate sensitivity and specificity. METHODS: The Hepatocellular carcinoma Early Detection Strategy (HEDS) study, a multi-center initiative of the National Cancer Institutes’ (NCI) Early Detection Research Network (EDRN), launched an effort to establish what has become the nation’s largest comprehensive biorepository and database on patients at high risk of developing HCC. The cohort has been developed in six clinical centers across the country. Subjects are enrolled for a five-year period involving data and specimen collection every six months in accordance with standard surveillance for HCC. Extensive clinical data are collected and specimens are stored at a central repository. RESULTS: The database and biorepository contain longitudinally collected clinical data and serum and plasma samples from 1482 participants with cirrhosis and without evidence of HCC at baseline. Fifty-six percent are male, 85% Caucasian, 30% have a history of chronic HCV and 71% have compensated cirrhosis. CONCLUSIONS: The HEDS cohort provides opportunities for the continued study of the incidence and course of HCC in a comprehensively followed population of patients at high risk for this malignancy. Further, the EDRN biorepository provides a distinct opportunity for the development of novel biomarkers.